2020
DOI: 10.1038/s41398-020-01036-5
|View full text |Cite
|
Sign up to set email alerts
|

Common and distinct patterns of intrinsic brain activity alterations in major depression and bipolar disorder: voxel-based meta-analysis

Abstract: Identification of intrinsic brain activity differences and similarities between major depression (MDD) and bipolar disorder (BD) is necessary. However, results have not yet yielded consistent conclusions. A meta-analysis of whole-brain resting-state functional MRI (rs-fMRI) studies that explored differences in the amplitude of low-frequency fluctuation (ALFF) between patients (including MDD and BD) and healthy controls (HCs) was conducted using seed-based d mapping software. Systematic literature search identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
112
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(131 citation statements)
references
References 83 publications
12
112
3
4
Order By: Relevance
“…Abnormal structure and function in the cerebellum have been demonstrated in MDD patients ( 73 ), including abnormalities of gray-matter volume ( 74 , 75 ), glucose metabolism ( 76 , 77 ), functional activity, and connectivity ( 78 84 ). A previous meta-analysis demonstrated decreased sALFF in the bilateral cerebellum in MDD ( 85 ), which was in line with our results. Moreover, the current findings of increased dALFF (more variability) in cerebellum were in line with previous studies and may reflect the instability of neurofluctuation and information integration in MDD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Abnormal structure and function in the cerebellum have been demonstrated in MDD patients ( 73 ), including abnormalities of gray-matter volume ( 74 , 75 ), glucose metabolism ( 76 , 77 ), functional activity, and connectivity ( 78 84 ). A previous meta-analysis demonstrated decreased sALFF in the bilateral cerebellum in MDD ( 85 ), which was in line with our results. Moreover, the current findings of increased dALFF (more variability) in cerebellum were in line with previous studies and may reflect the instability of neurofluctuation and information integration in MDD patients.…”
Section: Discussionsupporting
confidence: 93%
“…This approach may even increase our ability to uncover crucial alterations in mood disorders beyond specific diagnostic categories and thus help refine the current, historically defined divisions between these categories ( Biswal, 2021 ). Examples of this are numerous ( Gong et al, 2020 , Luo et al, 2021 ). For instance a recent metanalysis of whole- brain rs-fMRI studies on ALFF in MDD and BD patients found aberrant regional intrinsic cerebral activity in common brain areas (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, they also find that increasing ALFF of the right insula was significantly greater in BD than MDD, which suggested that the impairment of cognition function in BD might be more severe than that in UD. Moreover, several regions, including the limbic system and occipital cortex, differed between conditions, indicating that these disorders may be associated with spatially distinct patterns of brain function ( 32 ). A previous triple-network model study (involving the default mode network, central executive network, and salience network, which is associated with cognitive function, such as attention and working memory) also provided evidence about the shared and specific functional and structural alterations in BD and MDD ( 33 ).…”
Section: Discussionmentioning
confidence: 99%